Dynamic changes in oxytocin receptor expression and activation at parturition in the rat brain - Meddle, Simone L; Bishop, Valerie R; Gkoumassi, Effimia; van Leeuwen, Fred W; Douglas, Alison J (Endocrinology (Philadelphia), 2007)
Oxytocin plays a pivotal role in rat parturition, acting within the brain to facilitate its own release in the supraoptic nucleus (SON) and paraventricular nucleus, and to stimulate maternal behavior. We investigated oxytocin receptor (OTR) expression and activation perinatally. Using a (35)S-labeled riboprobe complementary to OTR mRNA, OTR expression was quantified in proestrus virgin, 21- and 22-day pregnant, parturient (90 min. from pup 1 birth), and postpartum (4-12 h from parturition) rats. Peak OTR mRNA expression was observed at parturition in the SON, brainstem regions, medial preoptic area (mPOA), bed nucleus of the stria terminalis (BnST), and olfactory bulbs, but there was no change in the paraventricular nucleus and lateral septum. OTR mRNA expression was increased on the day of expected parturition in the SON and brainstem, suggesting that oxytocin controls the pathway mediating input from uterine signals. Likewise, OTR mRNA expression was increased in the mPOA and BnST during labor/birth. In the olfactory bulbs and medial amygdala, parturition induced increased OTR mRNA expression compared with pre-parturition, reflecting their immediate response to new stimuli at birth. Postpartum OTR expression in all brain regions returned to levels observed in virgin rats. Parturition significantly increased the number of double-immunolabeled cells for Fos and OTR within the SON, brainstem, BnST, and mPOA regions compared with virgin rats. Thus, there are dynamic region-dependent changes in OTR-expressing cells at parturition. This altered OTR distribution pattern in the brain perinatally reflects the crucial role oxytocin plays in orchestrating both birth and maternal behavior.